Dynamics of M1 macrophages in oral mucosal lesions during the development of acute graft-versus-host disease in rats. (28th September 2017) - Seno, K; Yasunaga, M; Kajiya, H; Izaki-Hagio, K; Morita, H; Yoneda, M; Hirofuji, T; Ohno, J
Summary: The role of macrophage infiltrates in oral mucosal acute graft- versus -host disease (AGVHD) remains unclear, although clinical studies suggest that macrophage infiltration correlates directly with the severity of AGVHD. In this study, we investigated the role of M1 macrophage infiltration in the oral mucosa of rats with AGVHD. Lewis rat spleen cells were injected into (Lewis × Brown Norway) F1 rats to induce systemic GVHD. Tongue samples were evaluated using histology, immunohistochemistry, dual immunofluorescence, real-time reverse transcription–polymerase chain reaction, Transwell migration assays and Stamper–Woodruff binding assays. At the onset of oral mucosal AGVHD, dual immunofluorescence and migration assays revealed that M1 macrophages had accumulated in the basement membrane (BM) region via the laminin/CD29 β1 integrin pathway. Macrophage-secreted matrix metalloproteinase-2 was related to BM degradation. The adhesion of macrophages to the oral epithelium could be inhibited by pretreating macrophages with a CC chemokine receptor 2 (CCR2) antibody and/or pretreating lesion sections with monocyte chemoattractant protein-1 (MCP-1) antibody. Our data show that the migration and adhesion of M1 macrophages are associated with oral mucosal AGVHD, which is mediated in part by both laminin/CD29 β 1 intern and MCP-1/CCR2 pathways. Therefore, our study provides additional support for the contribution of macrophage infiltrate to the development of oral mucosal AGVHD. Graphical Abstract: